PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATERI PERENCANAAN DAN PENGALAMATAN JARINGAN KELAS XI TKJT DI SMKNEGERI 2 PADANG PANJANG - Ramadhani, Tesa Amalia; Mulyono, Heri; Darman, Regina Ade (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The purpose of this research is to produce Android-based learning media using the valid Articulate stroyline 3 application Produce Android-based learning media using the practical Articulate stroyline 3 application. This research method uses the Research and Development (RD) method. The results of the study tested the practicality of android-based learning media from teacher practicality data of 90.74% with the category of very practical. Meanwhile, student responses were obtained with 88.17% with the category of very practical. Thus, it can be concluded that the response of teachers and students to android-based learning media is very practical, so that it can be used in the learning process at school.